2019
DOI: 10.6009/jjrt.2019_jsrt_75.11.1297
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Application to Radiation Protection Education by Four-dimensional Visualization of Scatter Distribution in Radiological Examination Using Virtual Reality

Abstract: Purpose: When working on fluoroscopy and patient assistance in a healthcare facility, workers need to understand how to properly protect scattered radiation. In this study, we examined a four-dimensional visualization method to make it easy to understand the spread of scattered radiation visually, and proposed its application to radiation protection education. Methods: We constructed the X-ray room, X-ray CT room, and angiography room using Particle Heavy Ion Transport code System (PHITS), and calculated the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Although it was at the level of an animal experiment, there is a report that use of AR in confirming the position of a skin puncture needle reduced the dose-area product of subject exposure by 37% [26]. The possibility has also been reported that visualization of the distribution of scattered radiation in medical settings using VR [27], AR [28,29], and projection mapping [30] technology will lead to increased exposure awareness in medical professionals and a higher effect of protection education. To the best of our knowledge, however, there have been no reports about training using AR applications to educate medical staff working in hospitals on the utility and proper use of ceiling-suspended radiation shielding screens, which are considered to be essential equipment in protecting staff performing IR from radiation.…”
Section: S5mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was at the level of an animal experiment, there is a report that use of AR in confirming the position of a skin puncture needle reduced the dose-area product of subject exposure by 37% [26]. The possibility has also been reported that visualization of the distribution of scattered radiation in medical settings using VR [27], AR [28,29], and projection mapping [30] technology will lead to increased exposure awareness in medical professionals and a higher effect of protection education. To the best of our knowledge, however, there have been no reports about training using AR applications to educate medical staff working in hospitals on the utility and proper use of ceiling-suspended radiation shielding screens, which are considered to be essential equipment in protecting staff performing IR from radiation.…”
Section: S5mentioning
confidence: 99%
“…In recent years, virtual reality (VR) and augmented reality (AR) technology have been used in the field of medicine for training healthcare staff [16][17][18] and assisting physician's procedures [19][20][21][22][23][24][25][26]. The possibility has also been reported that visualization of the distribution of scattered radiation using VR [27], AR [28,29], and projection mapping [30] technology will lead to increased exposure awareness in medical staff and an efficient tool in their formative education and continuing development for radiation protection.…”
Section: Introductionmentioning
confidence: 99%
“…As scattered radiation is not visible, visualisation is necessary to learn about its behaviour. Visualisation studies on the behaviour of scattered radiation include studies using augmented reality (AR) and virtual reality (VR) [3][4][5]. There are studies that use AR to visualise scattered radiation in various ways during examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) view is made possible by using AR and VR, as against the 2D view presented in textbooks. There are reports that the use of AR and VR in teaching materials attracted interest in users [4,5,8]. However, most studies that use AR and VR to visualise scattered radiation require special equipment, such as dedicated cameras and head-mounted displays [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, we developed a highly accurate radiation behaviour calculation technology and virtual reality system. We created an augmented reality environment using Monte Carlo simulations to make it easier for people unfamiliar with the behaviour of radiation to visually understand the spread of scattered radiation [8,9]. In addition to the fixed-point dose evaluation during radiological treatment, three-dimensional (3D) data of the scattered radiation distribution and a four-dimensional (4D) visualisation video with a time axis were created.…”
Section: Introductionmentioning
confidence: 99%